Global Disruptions in Seafood Trade during COVID-19 : The Effects of Mobility Restrictions on Crustacean Exports from Indonesia, Thailand, and Vietnam - Pratiwi, Ayu; Lee, Guenwoo; Marjanen, Heli; Kettunen, Erja (Routledge, 2026)
The COVID-19 pandemic disrupted global supply chains due to the stringent limitations on the movement of people and goods. Although the impacts of mobility restrictions on global food trade have been studied, their implications for specific commodities have yet to be thoroughly investigated. This paper explores Indonesian, Thai and Vietnamese crustacean exports from April 2019 to April 2021, that is, the time preceding the pandemic and that following the first strict lockdowns (SLD) and employs a three-way fixed effects estimation and event study regression. No statistically significant difference in crustacean export performance between pre- and post-SLD periods was detected in these three countries. However, estimation results show that the first SLD is associated with an increase in Vietnam’s crustacean export value and a decline in Thailand’s export volume and value. No such effects were observed in Indonesia. Vietnam seemed to manage the pandemic effectively by imposing a centralized policy and succeeding in increasing crustacean exports despite the disruptions. The future of global seafood trade will likely be subject to fast-changing global geopolitics, with countries potentially re-evaluate their primary trading partners, influenced not only by economic and foreign policy interests but also by the ramifications of their COVID-19 experiences.
Geoeconomics of the Sustainable Development Goals